Utilization of Alert System in Attendance Assessment as an Early Warning Media - Qurotul Aini; Taqwa Hariguna; Meilinda Lana Yahya (CCIT Journal, 2020)
All fields have been supported by technology, especially in the world of education in the teaching and learning process. In college absenteeism is a very important thing to show the presence of students where to determine the achievement of learning outcomes. Student guidance attendanceactivities can take place well and smoothly with very active students attending each student's attendance at completing research. However, at present, a problem is identified in the delivery of information on the results of the guideline absenteeism, namely there are still many students who donot pay attention to attendance guidance who should attend absences and after completing the guidance must be absent again and many students forget to be re-absent after completing guidance. Raharja College has implemented an online attendance assessment system, namely PenA (AttendanceAssessment) which is a proof of the development of information systems in terms of education. Which was developed to provide information regarding the results of Assessment of Attendance Guidance to students quickly through Rinfo email. There are 10 (ten) studies of literature in this study that dealwith the media for delivering information via Email. Alerts play an important role as student reminders in conducting attendance guidance. With the email notification system in the PenA system, it is very helpful for students regarding the results of guidance through Rinfo email that will be sentautomatically after the student attendance attendance. So that it can be concluded that email notification on the PenA system automatically helps 2 (two) parties at Raharja University. Where in the attendance process student guidance becomes more effective and more enthusiastic in conductingguidance.